The Fernow Watershed Acidification Study - Adams, Mary Beth.; DeWalle, David R.; Hom, John L.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
The Fernow Watershed Acidification Study is a long-term, paired watershed acidification study, undertaken in the central Appalachian Mountains of West Virginia, USA. The Study, which began in 1989, includes research on biogeochemical responses of streams, soils and vegetation to air pollution, and also includes research on acidification's effects on salamanders. This book describes the responses to chronic N and S amendments by deciduous hardwood forests, one of the few studies to focus on these important hardwood forest ecosystems. Intensive monitoring of soil solution and stream chemistry, along with measurements of soil chemistry, and vegetation growth and chemistry, provide insights into the acidification process in forested watersheds, evaluating these in the context of nitrogen saturation, soil acidification and base cation leaching models. This volume will be of interest to researchers, ecosystem modellers, managers and policy-makers concerned with the effects of air pollution on forested ecosystems.
to the Fernow Watershed Acidification Study -- Fernow and the Appalachian Hardwood Region -- Soil Chemical Response to Experimental Acidification Treatments -- Soil Water and Stream Water Chemical Responses -- Vegetation and Acidification -- Response of Salamanders to Experimental Acidification Treatments -- Acidification and Nutrient Cycling -- Implications for Forest Ecosystem Sustainability and Resiliency -- Conclusions and Recommendations from the Fernow Watershed Acidification Study.
Keywords: LIFE SCIENCES; APPLIED ECOLOGY; ENDANGERED ECOSYSTEMS; ECOLOGY; FORESTS AND FORESTRY; ENVIRONMENTAL PROTECTION; LIFE SCIENCES; APPLIED ECOLOGY; ECOSYSTEMS; TERRESTIAL ECOLOGY; FORESTRY; ATMOSPHERIC PROTECTION/AIR QUALITY CONTROL/AIR POLLUTION